Dynamic behavior of UHPC member under lateral low-velocity impact: Mesoscale analysis. (February 2023) - Peng, Q.; Wu, H.; Jia, P.C.; Ma, L.L.
Highlights: Full CSC model parameters for UHPC cementitious matrix are calibrated and validated. Bond behavior between fibers and matrix is examined experimentally and numerically. Mesoscale model and analysis approach are verified at both material and member levels. Influence of fiber volume fraction on dynamic behavior of UHPC member is evaluated. Abstract: Ultra-High Performance Concrete (UHPC), which mainly consists of the cementitious matrix and incorporated fibers, has superior impact-resistance compared with the normal strength concrete. Concerning the impact-resistant evaluation and performance-based design of UHPC structure under lateral low-velocity impact, a mesoscale modeling analysis approach considering the bond-slip behavior between random distributed fibers and cementitious matrix of UHPC is proposed. Firstly, the Continuous Surface Cap (CSC) model parameters for the matrix of UHPC were calibrated, and validated through a series of fundamental mechanical tests and low-velocity impact test. Secondly, by conducting a single steel fiber pull-out test, the fiber-matrix interaction was examined, and an appropriate interaction algorithm considering bond-slip effect was employed in the commercial program LS-DYNA. Then, the mesoscale model of UHPC was established through a self-coding program in MATLAB. The reliability of the mesoscale model and analysis approach were systematically verified at both material level (uniaxial compression, uniaxial tension, three- and four-point bending tests) and member level (total 15 low-velocity impact scenarios considering various member types, sectional shapes, sectional dimensions, and compressive strength). Finally, the influence of fiber volume fraction on the dynamic behavior of UHPC member was examined. It derives that the incorporated fibers can help reduce the lateral deflections and avoid the brittle punching-shear failure mode of UHPC members, and the optimal fiber volume fraction of 1.5% for the impact-resistant design is recommended. The present work provides a new way to accurately and conveniently evaluate the low-velocity impact-resistance and predict the dynamic behavior of the arbitrary configured UHPC structure.